Location choice of German multinationals in the Czech Republic: The importance of agglomeration economies - Veronika Hecht (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2015)
This paper analyses the location choice of German investors in the Czech Republic based on a unique dataset covering all Czech companies with a German equity holder in 2010. The identification of the regional determinants of foreign direct investment (FDI) location is an important regional policy issue as FDI is supposed to improve the labour market conditions of the host region. Using a nested logit approach the impact of agglomeration economies, labour market conditions and distance on the location choice decision is investigated. The main result of the paper is that apart from a low distance to the location of the parent company the attractive-ness of a Czech district for German investors is mainly driven by agglomeration economies. Besides localisation economies the agglomeration of German compa-nies in a region plays a decisive role. The importance of labour market characteris-tics differs between investment sectors, sizes and periods. – – Auf Basis eines einzigartigen Datensatzes, der alle tschechischen Unternehmen umfasst, die im Jahr 2010 einen deutschen Kapitaleigener aufwiesen, analysiert dieses Papier die Standortwahl von deutschen Investoren in Tschechien. Die Identifikation der regionalen Determinanten von ausländischen Direktinvestitionen ist ein wichtiges regionalpolitisches Thema, da ausländische Direktinvestitionen zu einer Verbesserung der Arbeitsmarktbedingungen in der Zielregion beitragen sollen. Anhand eines nested logit-Ansatzes wird der Einfluss von Agglomerationseffekten, Arbeitsmarktbedingungen und Distanz auf die Standortwahl von ausländischen Investoren untersucht. Das zentrale Ergebnis des Papiers ist, dass für die Attraktivität einer tschechischen Region für deutsche Investoren neben der geringen Distanz zum Standort des deutschen Mutterunternehmens insbesondere Agglomerationseffekte ausschlaggebend sind. Neben Lokalisationseffekten spielt die Agglomeration von deutschen Unternehmen in einer Region eine entscheidende Rolle. Die Bedeutung von Arbeitsmarkteigenschaften unterscheidet sich zwischen Investitionssektoren, -größen und -zeiträumen.
Keywords: F23; R12; R30; 330; Location choice; FDI; Multinational enterprises; Germany; Czech Republic; Agglomeration Economies